Biotechnology and its contribution to the agricultural economy: Using microbes for increasing crop yields - Nazarova Nadezhda; Sazhneva Lioubov; Sakhbieva Amina; Kokhreidze Murman (BIO Web of Conferences)
The article analyses the significant role of biotechnology in the development of the agricultural economy, focusing on the use of microorganisms to increase crop yields. Biotechnology based on interaction with microbes represents an innovative approach that contributes to sustainable agriculture and optimization of production processes. The article elaborates on the various applications of microorganisms, including the use of nitrogen-fixing bacteria to increase soil nutrient content, phosphate-mobilizing microbes, and microorganisms involved in pathogen suppression and plant defense against diseases and stressors. Special attention is paid to biological fertilizers and biopesticides, which help to reduce the use of chemical agents, which in turn reduces harmful effects on the environment and human health. The prospects for using microbes to increase plant resistance to climate change, improve soil structure and quality, and optimize water use are discussed. The paper also analyses the economic benefits of microbial biotechnology in the agricultural sector, including reduced costs of chemical fertilizers and pesticides, as well as increased efficiency of agricultural production through increased yields. Successful examples of microbial technologies in agriculture and their contribution to global food security are highlighted. In conclusion, it is emphasized that the use of microorganisms in agriculture is a promising area that can not only increase yields and product quality, but also make a significant contribution to the sustainable development of the agro-industrial complex.